Personal Factors Affecting Intentions of Safe Vegetable Purchases in Danang City, Vietnam - Tinh, Luong; Dung, Doan Gia; Binh, Bui Quang; Truc, Bui Thi Mai (Asian Journal of Agriculture and Rural Development, 2020)
This study determined the relationships between personal factors and intentions of safe vegetable purchases in Danang City, Vietnam. The study added two new factors, communication and awareness of responsiveness of supermarkets, which are correlated to purchase intentions of consumers. Consumer behaviours was surveyed in Danang City from April to June 2019, and analysed by a multivariate regression model. The result indicated that the intentions of safe vegetable purchases were associated with several factors such as perception of benefit - environment, perception of quality, subjective norms, awareness of supermarket responsiveness, barriers and habits. Unlike previous studies, this study found that the awareness of supermarket responsiveness and active communication of customers is statistically strongly correlated to safe vegetable purchases in Da Nang City. The findings suggested some implications for policy makers, authorities, and consumers in promoting behaviors of purchasing safe vegetables.